Effectiveness of Using Silicone Tape in Blepharoptosis - M. Sh, Khakimova (American Journal of Biomedicine and Pharmacy, 2025)
Congenital anomalies of the organ of vision are currently the main form of ophthalmopathology in childhood. This is confirmed by leading experts in pediatric ophthalmology (Avetisov ES, Khvatova AV, Kovalevsky EI - 1989). Among congenital defects of the organ of vision, blepharoptosis is in the first place. The ptosis of the upper eyelid, even partially, is a significant cosmetic defect. Complex forms of ptosis (according to various authors, in 44.35% of cases) especially worsen the appearance of patients, in which the ptosis of the eyelid is combined with other pathological diseases of the eye and oculomotor apparatus (blepharophimosis, epicanthus, paralytic strabismus, etc.). Eliminating ptosis in children is not just a cosmetic problem, as timely treatment of this pathology helps prevent a number of complications associated with ptosis - amblyopia, incorrect head position, impaired binocular vision, and poor posture.